Survivors of the Shoah: Interviewee: Endre Kadar Part I (Survivors of the Shoah Visual History Foundation, 1999)
Shoah Foundation interview code: 49558 Duration: 01:58:00 Interview with Hungarian Holocaust survivor Endre Kadar. The tape is part of a collection of 10 interviews provided to OSA by the Survivors of the Shoah Visual History Foundation. Interviewer: Judit Burg.